IN VITRO PROPAGATION OF THE HOANG THAO SAP (DENDROBIUM CREPIDATUMLINDL. & PAXT. )- A VALUE ORCHID VARIETY - Kết, Nguyễn Văn; Vinh, Nguyễn Văn (Vietnam Journal of Science and Technology, 2012)
SUMMARYIt is outlined for four experiments on invitro propagation of Dendrobium crepidatum Lindl.& Paxt. The treatment with Vacin Went medium  reached the highest results, plant height (2.8 cm), numbers of roots (5.0), root length (2.3  cm), and numbers of multiple shoot formation (5.2). In addition, Dendrobium crepidatum in Vacin  Went media gave the best fresh yield (255.4 mg), lower Hyponex (180.5 mg), and lowest ½  MS (130.7 mg). Dry weight of plants from Vacin Went media also showed the highest result (21.5 mg). BA containing media indicated remarkable effects in shoot formation to  TDZ.. BA suplemented media (0.5 mg/l) attained the highest increase 6.8 shoots/shoot clumps, fresh weight 426.7 mg, and dry weight 36.8 mg. It can be said that the higher concentration of plant growth regulator is, the lower the final fresh and dry weight are.